Increased frequencies of CD8+CD57+ T cells are associated with antibody neutralization breadth against HIV in viraemic controllers. Issue 1 (9th December 2016) - Palmer, Christine D; Romero‐Tejeda, Marisol; Scully, Eileen P; Lockhart, Ainsley; Seaman, Michael S; Goldenthal, Ariel; Piechocka‐Trocha, Alicja; Walker, Bruce D; Chibnik, Lori B; Jost, Stephanie; Porichis, Filippos
Abstract : Introduction: An effective prophylactic vaccine against HIV will need to elicit antibody responses capable of recognizing and neutralizing rapidly evolving antigenic regions. The immunologic milieu associated with development of neutralizing antibody breadth remains to be fully defined. In this study, we sought to identify immunological signatures associated with neutralization breadth in HIV controllers. We applied an immune monitoring approach to analyze markers of T cell and myeloid cell activation by flow cytometry, comparing broad neutralizers with low‐ and non‐neutralizers using multivariate and univariate analyses. Methods: Antibody neutralization breadth was determined, and cryopreserved peripheral blood mononuclear cells were stained for T cell and myeloid cell activation markers. Subjects were grouped according to neutralization breadth, and T cell and myeloid cell activation was analyzed by partial least squares discriminant analysis to determine immune signatures associated with high neutralization breadth. Results: We show that neutralization breadth in HIV viraemic controllers (VC) was strongly associated with increased frequencies of CD8 + CD57 + T cells and that this association was independent of viral load, CD4 count and time since HIV diagnosis. Conclusions: Our data show elevated frequencies of CD8 + CD57 + T cells in VC who develop neutralization breadth against HIV. This immune signature could serve as a potential biomarker of neutralization breadth and should be further investigated in other HIV‐positive cohorts and in HIV vaccine trials.